Effects of Sibseonsan as an Anti-Inflammatory, Anti-Wrinkle, and Skin Whitening Treatment - Na Young Jo (MEDrang Inc., 2020)
Background The purpose of this study was to investigate whether Sibseonsan (SSS) is an effective anti-inflammatory, anti-wrinkling, and whitening agent. Methods To determine whether SSS had an anti-inflammatory effect, a murine macrophage cell line was used (RAW 264.7) and production of DPPH, NO, TNF-α, and PGE2 were measured. To ascertain potential anti-wrinkle effects of SSS in these cells, collagenase and elastase production were measured. To verify whether SSS had a whitening effect, tyrosinase activity and DOPA staining were performed using a melanoma cell line (B16/F10). Results There was no significant reduction in survival of SSS-treated RAW 264.7 cells, up to 400 μg/mL. Free radical scavenging (23.96 ± 1.85%) was observed in RAW 264.7 cells treated with SSS at a concentration of 400 μg/mL. The SSS treatment group (400 μg/mL) significantly inhibited NO production compared with the LPS stimulated treatment group. The SSS treatment of macrophage cells appeared to reduce production of TNF-α in a concentration dependent manner. There was a significant reduction in the concentration of PGE2 by about 25% in the SSS treatment (400 μg/mL) group (p = 0.05). Compared with the control, the production of collagenase and elastase in B16/F10 cells treated with SSS (400 μg/mL) was greater by 26.37% and 45.71%, respectively. The SSS treatment (400 μg/mL) group showed a significant reduction by about 17% in tyrosinase production in B16/F10 cells. The SSS treatment group showed little change in DOPA staining. Conclusion SSS extract may be useful for the treatment and prevention of inflammatory diseases and may have anti-wrinkle and whitening effects. These results may support the use of SSS in clinical practice.